Diseño, añalisis e interpretación de indicadores de gestión para la empresa "Tecnicentro servifaconza" en la ciudad de Quito, Distrito metropolitano periodo 2008. - Espinosa Basantes, Wendy Priscila (2010)
Abstract: The present project of design, analysis and interpretation of management indicators for the company Tecnicentro Servifaconza of the province of Pichincha, Quito canton consists of three chapters in which it is detailed: The current situation of the company, an X-ray that comes to make the organization chart , it is determined labor aspects of functions and responsibilities of the personnel, map of processes that are carried out within Servifaconza, the information obtained in this chapter serves for the development of proposals that allow to improve the future business situation. Research continues with the theoretical basis on which the present project is based, specific financial indicators, management indicators, new tools to support business management (balanced scorecard) and the application of these in the organizational environment. With the information obtained from chapters I and II, Chapter III was developed in which relevant areas, variables and objectives are determined, a design of indicators table applicable to Servifaconza is included, the analysis and interpretation of the information in In the areas of administration, sales and marketing, a report addressed to the company Servifaconza is attached with the result of the research carried out on the company and finally the respective conclusions and recommendations of the research are formulated. The importance of the Current use of management indicators in addition to traditional financial indicators.